The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/bies.202100137
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of SARS‐CoV‐2 is consistent with both natural or laboratory origin: Response to Tyshkovskiy and Panchin (10.1002/bies.202000325)

Abstract: Tyshkovskiy and Panchin have recently published a commentary on our paper in which they outline several "points of disagreement with the Segreto/Deigin hypothesis." As our paper is titled "The genetic structure of SARS-CoV-2 does not rule out a laboratory origin," points of disagreement should provide evidence that rules out a laboratory origin. However, Tyshkovskiy and Panchin provide no such evidence and instead attempt to criticize our arguments that highlight aspects of SARS-CoV-2 that could be consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(20 reference statements)
0
8
0
1
Order By: Relevance
“…The authors responded that: "we never claim that RaTG13 itself is a 'proposed ancestor' or the backbone used for a possible construction of SARS-CoV-2″ and emphasized that their hypothesis was about a "RaTG13-like backbone and an RBD from a MP789-like pangolin CoV". [2] Although the authors didn't claim that RaTG13 itself was an ancestor of SARS-CoV-2 in their article in Bioessays, they explicitly and repeatedly stated that in other resources, including their online blogs: "And CoV2 is an obvious chimera (though not nesessarily a lab-made one), which is based on the ancestral bat strain RaTG13, in which the receptor binding motif (RBM) in its spike protein is replaced by the RBM from a pangolin strain, and in addition, a small but very special stretch of four amino acids is inserted, which creates a furin cleavage site that, as virologists have previously established, significantly expands the "repertoire" of the virus in terms of whose cells it can penetrate". [11] Remarkably, the blog post hasn't been corrected after our commentary as we are writing this response.…”
Section: Points Of Disagreement With the Segreto / Deigin Hypothesismentioning
confidence: 99%
See 4 more Smart Citations
“…The authors responded that: "we never claim that RaTG13 itself is a 'proposed ancestor' or the backbone used for a possible construction of SARS-CoV-2″ and emphasized that their hypothesis was about a "RaTG13-like backbone and an RBD from a MP789-like pangolin CoV". [2] Although the authors didn't claim that RaTG13 itself was an ancestor of SARS-CoV-2 in their article in Bioessays, they explicitly and repeatedly stated that in other resources, including their online blogs: "And CoV2 is an obvious chimera (though not nesessarily a lab-made one), which is based on the ancestral bat strain RaTG13, in which the receptor binding motif (RBM) in its spike protein is replaced by the RBM from a pangolin strain, and in addition, a small but very special stretch of four amino acids is inserted, which creates a furin cleavage site that, as virologists have previously established, significantly expands the "repertoire" of the virus in terms of whose cells it can penetrate". [11] Remarkably, the blog post hasn't been corrected after our commentary as we are writing this response.…”
Section: Points Of Disagreement With the Segreto / Deigin Hypothesismentioning
confidence: 99%
“…In the end, the authors concluded that we have "underestimated the probability of a 12-nt insertion not containing a 5+ restriction enzyme cut site by 2 orders of magnitude: rather than the 0.5% implied by their [our] calculation, the actual probability is around 50%". [2] We could discuss which statistical models and assumptions are more reasonable in the given circumstances. However, this is not necessary, since the smallest probability achieved by Segreto and Deigin in their own calculation (p = 0.468) is still far higher, by an order of magnitude, than the relaxed threshold (p = 0.05) used to reject the null hypothesis in statistical analysis.…”
Section: Points Of Disagreement With the Segreto / Deigin Hypothesismentioning
confidence: 99%
See 3 more Smart Citations